Lessons from accidents during tunnel construction. (July 2021) - Sousa, Rita L.; Einstein, Herbert H.
Highlights: Large database of tunnel accidents worldwide with case details and data analysis. Description of common type of tunnel accidents, causes and consequences. Influence diagrams for each type of accident with main factors and interactions. Abstract: The number and complexity of tunnel systems will surely increase with ever increasing population and urbanization. Although most tunnel construction projects have been completed safely, there have been several incidents that have resulted in delays, cost overruns, and sometimes more significant consequences such as injury and loss of life. In this paper we present a database of tunnel accidents that occurred during construction containing 206 cases that were collected from a combination of literature review, newspapers, and correspondence with tunneling experts around the world. This paper describes the data collection and the results of the data analysis. The study of the accidents in the database made it possible to identify and categorize accidents into different types, typical causes, and consequences, as well as identify the scenarios in which these events (accidents) are more likely to occur. The analysis of the database shows that unexpected ground conditions are often the main reason for tunneling accidents during construction. Despite recent efforts made to improve existing tunneling technologies, forecasting ground conditions in tunneling remains the most challenging task in tunneling because of significant uncertainties related to the subsurface. The study of the different cases of the database made it possible to identify different scenarios, in which these events are most likely to occur. As a result of the analysis, influence diagrams were constructed for each type of accident containing the main factors, and the interactions between them. To emphasize: the objectives of the paper are: 1. To provide information on tunnel accidents and the related data collection process and 2. Present a process with which the information can be systematically evaluated.